Personal development in the information and library profession - Webb, Sylvia P. (Europa Pub. LondonGB, 2003)
Defines personal development in the context of the information and library profession, whilst not losing sight of the need to view it in a wider organisational setting. Discusses what personal development can contribute to the respective performances of the individual, the information service and the organization.